SPICES PLANT AS BIOINSECTICIDES FOR CONTROLLING MAIZE WEEVIL SITOPHILUS ZEAMAIS (MOSTCH) Pemanfaatan Tanaman Rempah sebagai Pestisida Nabati untuk Penanggulangan Hama Kumbang Bubuk Jagung Sitophilus zeamais (Mostch) - Arrahman, Ayyub; Saenong, Muhammad Sudjak (Badan Penelitian dan Pengembangan Pertanian, 2020)
Indonesia has numerous and varied natural resources of spices plant which grow at almost all theregions. These plants can grow and adapt to the slightly diverse agroecological conditions and agroecosystems, from dry to wet. In general, the utilization of these plants by the community is still limited as ingredients and spices for culinary and flavoring instead of the potential of bioactive compounds contained therein. These resourcesare very useful and effective utilized asbioinsecticides to eradicate plant pests and diseases, as well as medicine for human. This paper discussed the benefits and efficacy of several spiceplants, namely lemongrass, shallots, garlic, sweet and chili peppers, clove, sand ginger (kencur), and pepper as herbicides at various levels of dosage and treatments. This manuscript also discussed the constraints and development strategies, and aimed to provide information on the science and technology in controlling the Sitophilus zeamais (Motsch) pests in corn kernels during the storage period. It is expected that this paper would be useful for the policy makers, academicians, researchers and practitioners who have the competence to deal with beetle pest problems.Keywords: Spices, bioinsecticides, Sitophilus zeamais (Motsch), controllingÂ AbstrakTanaman rempah yang tumbuh di hampir seluruh wilayah Indonesia sangat beragam. Tanaman ini beradaptasi pada berbagai agroekologi dan agroekosistem, mulai dari wilayah beriklim kering sampai beriklim basah. Pemanfaatan tanaman ini oleh masyarakat umumnya masih terbatas sebagai bahan rempah dan bumbu kuliner, penyedap masakan dan cita rasa, padahal senyawa bioaktif yang terkandung di dalamnya potensial sebagai pestisida nabati untuk membasmi hama penyakit tanaman dan bahan obat kesehatan manusia. Tulisan ini membahas manfaat dan kemanjuran dari beberapa tanaman rempah, yakni tanaman sereh, bawang merah, bawang putih, lombok merah, cengkeh, kencur, dan lada sebagai pestsisida nabati dalam berbagai dosis dan ragam perlakuan. Kendala dan strategi pengembangan pestisida nabati bagi penggulangan hama kumbang bubuk perlu mendapat perhatian yang tidak saja untuk kepentingan masyarakat luas, namun diperlukan sebagai informasi ilmu dan teknologi penanganan hama secara terpadu.Kata kunci: tanaman rempah, bioinsektisida, hama kumbang bubuk, pengendalian